Effects of a single bout of exercise on human hemocytes and serum interleukin 3, erythropoietin, and soluble transferrin receptor in a hot and humid environment - Yuhu Lv; Lin Cheng; Xiqian Zhang; Fenglin Peng; Yu Yuan; Xiquan Weng; Wen-Tao Lin (PeerJ)
Background Exercise in humid and hot environments (HHEs) may result in decreased perception, motor performance, and memory owing to endogenous heat production and exogenous load. However, whether a single bout of exercise (SBOE) intensity affects the magnitude of changes in the levels of hemocytes remains controversial. In this article, we aimed to investigate the effects of a SBOE of varying intensities on blood cells in HHE. Methods Thirty-two volunteers were randomly divided into a quiet control group (QC), 55% VO2max intensity exercise group (HHE55%), 70% VO2max intensity exercise group (HHE70%), and 85% VO2max intensity exercise group (HHE85%). The participants in the exercise groups were assigned to perform an SBOE on the treadmill under HHE conditions for 30 min, whereas participants in the QC remained still under HHE conditions for 30 min (temperature: 28–32 °C, relative humidity: 85–95%). Results The net body mass (NBM), perfusion index (PI), mean corpuscular volume (MCV), platelet (PLT), and plateletcrit (PCT) values were affected significantly by the exercise intensity (P < 0.01) the hemoglobin (HGB) and neutrophil count (NE) were affected significantly by exercise intensity (P < 0.05). After an SBOE, compared with that before exercise, the sublingual temperature (ST) of all groups, the NBM and MCV of all exercise groups, the PI of the HHE55% and HHE70% groups, the HGB, hematocrit (HCT), and NE of the HHE70% group, the red blood cell count (RBC), PLT, and PCT of the HHE70% and HHE85% groups, and the white blood cell count (WBC) of HHE85% changed very significantly (P < 0.01). The PCT of QC, blood oxygen saturation (SaO2), and soluble transferrin receptor (sTfR) levels in the HHE55% group, the lymphocyte count (LY) in the HHE70% group, and the HGB and HCT in the HHE85% group changed significantly (P < 0.05). Conclusion Low- and moderate-intensity SBOE in HHE could increase the serum EPO and serum sTfR levels and decrease the serum IL-3 levels. Conversely, a high-intensity load could increase the risk of inflammation. Therefore, low-intensity exercise may be more appropriate for an SBOE in HHE.